(untitled) (Journal of Scientific Research, 2026)
Gynura (G.) procumbens is a medicinal herb widely employed in Bangladesh to improve vitality. The main objective of this research was to characterize the bioactive constituents in G. procumbens leaves associated with both α-amylase inhibition and antioxidant potential. The extraction efficiency of G. procumbens was investigated using methanol, n-hexane, and different ethanol-water concentrations. The optimal solvent combination was determined by analyzing the relationship between the extraction yield and the potency of the resulting α-amylase inhibition and radical scavenging activities. The compounds were achieved through GC-MS, FTIR, and phytochemical analysis, which might be accountable for inhibition activity. The α-amylase inhibitory activity of methanolic and n-hexane extract were 9.54 and 8804.5 µg/mL, respectively. The total antioxidant capacities were estimated, and standard value of ascorbic acid was 0.358, whereas methanolic extract of G. procumbens was 0.244 and n-hexane was 0.072. A 100 % ethanol exhibited the highest scavenging potential (56.68 ± 0.40) μg/mL, and aqueous extract exhibited lowest potential (565.19 ± 0.38) μg/mL. Phenolics, carbohydrates, triterpenes and organic acids were identified as putative inhibitors against inhibitory activity. In conclusion, G. procumbens could be a potential herb used as a natural antioxidant and antidiabetic remedy.